2002
DOI: 10.1034/j.1600-0560.2002.59.x
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Patterns of Mammography Use: A Geographic Perspective on National Needs for Intervention Research

Abstract: Objective. To introduce a methodology for planning preventive health service research that takes into account geographic context. Design. Bayesian hierarchical modeling describes mammography as a function of county-level socioeconomic data and explicitly estimates the geographic variation unexplained by the county-level data. This model produces county use estimates (both NHIS-sampled and unsampled), which are aggregated for entire states. The locations of intervention research studies are examined in light of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 25 publications
0
20
0
Order By: Relevance
“…These findings support the need for ongoing efforts to strengthen and develop the healthcare infrastructures in communities considered to be underserved and outside of major urban cities. For example, as indicated by Legler et al, 44 the use of mobile mammogram vans may help increase screening rates in HPSAs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings support the need for ongoing efforts to strengthen and develop the healthcare infrastructures in communities considered to be underserved and outside of major urban cities. For example, as indicated by Legler et al, 44 the use of mobile mammogram vans may help increase screening rates in HPSAs.…”
Section: Discussionmentioning
confidence: 99%
“…3 Despite the known benefits of annual or biannual screening mammography beginning at age 40 or 50, 4 approximately 25%-50% of American women report not having a mammogram in the past 2 years. 4,5 High variation in average rates of screening mammography adherence can be attributed to the lack of consensus about the efficacy of screening for women aged [40][41][42][43][44][45][46][47][48][49], variation in availability of screening facilities, and other factors that may disproportionately impact those residing in communities with fewer healthcare resources. 6 Elting et al 7 documented that mammography facilities were available in only 49% of Texas counties.…”
mentioning
confidence: 99%
“…Some studies have found that socioeconomic variables affect health outcomes independently at both the neighborhood and the individual levels [38,39]. We therefore considered several variables from the 2000 Census for our study that have been shown previously to have independent association with mammography use [11,28,29]. Those included percentage of adults with HS diploma, percentage of persons in rural area, percentage of persons in suburban area, mammography facility located in a census tract, median family income, percentage of white collar workers, and median home values measured at the census tract level.…”
Section: Data Sets and Linkagementioning
confidence: 99%
“…Geographic accessibility to mammography facilities is an important contextual factor for mammography screening [11]. Only recently, with the advent of more local data, larger sample sizes, and the development of spatial analysis techniques, has it been possible to study geographic accessibility to cancer screening [12].…”
Section: Introductionmentioning
confidence: 99%
“…Although successful strategies to increase cancer screening among underutilizing populations have recently been reported, there has been unevenness in the targeting of intervention research, resulting in gaps in coverage. These gaps are evident geographically, which may warrant further investigation of the need for tailoring intervention research as well (Legler et al 2002). …”
Section: The Need For Small-area Estimatesmentioning
confidence: 99%